(untitled) (Research, Society and Development, 2021)
Objective: To verify in the literature data that confirm the antimicrobial properties and a toxicity profile of stingless indigenous bee hives of the genus Melipona. Methodology: Bibliographic review was carried out in the databases: Virtual Health Library (VHL), PubMed and Google academic. Articles, monographs, dissertations and theses were selected, dated between 2000 and 2020, in Portuguese and English. The search was carried out using the descriptors: stingless bees (Abelhas sem ferrão), antimicrobian activity (Atividade Antimicrobiana), honey (Mel) and toxicity (Toxicidade). And articles that were incomplete, or that were not within the pre-established time margin, and those that were duplicated were excluded from the research. Results: the results obtained were presented in relation to the main honey producing Melipona species, the predominant compounds responsible for biological activity, in addition to the description of the antimicrobial activity and the toxicity profile of the honeys mentioned in the files. Conclusion: The potential antimicrobial activity of the honeysuckle honey is verified, thanks to the plurality of active chemical and biological compounds present. Furthermore, the toxicity profile of these honeys is characterized, suggesting that the main cause of this condition is microbiological contamination.